A STUDY FACTORS OF POSITIVE COPING FOR NURSING STUDENTS UNDER THE MINISTRY OF DEFENSE - Pliankerd, Podchana; Prayai, Narulmon; Prasertsin, Ujsara (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to study factors of positive coping for nursing students under the ministry of defense. The sample of this research was four hundred seventy-two for nursing students who studying in the Bachelor of Nursing Science Program under the Ministry of Defense, Year 1 - 4, to be students in 3 places including the Royal Thai Army Nursing College the Royal Thai Air Force Nursing College and the Royal Thai Navy College of Nursing. The research instrument used for the study was positive coping for nursing students under the ministry of defense. The instrument used for data collecting was the five-level-rating scale total forty items with an index of item-objective congruence score of 0.60 - 1.00 with discrimination of 0.24 - 0.73 and a reliability coefficient of 0.94. The statistic used to analyze data comprising of frequency, percentage, mean, standard deviation, and confirmatory factor analysis. The result of the research found that the measurement model of positive coping for nursing students was fit with empirical data ( = 1.83 df = 2 p = .39 GFI = 1.00 AGFI = 0.99 CFI = 1.00 RMSEA = 0.00 SRMR = 0.00). This shows that the model has the goodness of fit with the empirical data and when analyzing the confirmation element model, it was found that the factor of each, in descending order as follows: preventive coping (SC = 0.95) proactive coping (SC = 0.85) reactive coping (SC = 0.75) and anticipatory coping (SC = 0.55). Further research should bring the positive coping elements of the students of nursing students to develop a group counseling program. For the students in the Bachelor of Nursing Science to have more positive coping.